2015
DOI: 10.3389/fnins.2015.00403
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of lithium in Parkinson's and other neurodegenerative diseases

Abstract: Lithium, the long-standing hallmark treatment for bipolar disorder, has recently been identified as a potential neuroprotective agent in neurodegeneration. Here we focus on introducing numerous in vitro and in vivo studies that have shown lithium treatment to be efficacious in reducing oxidative stress and inflammation, increasing autophagy, inhibiting apoptosis, and decreasing the accumulation of α-synulcein, with an emphasis on Parkinson's disease. A number of biological pathways have been shown to be involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 129 publications
(139 reference statements)
3
53
0
3
Order By: Relevance
“…[10,13] However, controlled clinical data demonstrating neuroprotection with clinical endpoints were lacking. The improvement in GDS we observed in the lithium arm is similar to the improvement noted by Letendre et al [8] (median improvement 0.29 while we found a median improvement of 0.47) in an open-label 12-week lithium study in patients with HAND.…”
Section: Discussionmentioning
confidence: 99%
“…[10,13] However, controlled clinical data demonstrating neuroprotection with clinical endpoints were lacking. The improvement in GDS we observed in the lithium arm is similar to the improvement noted by Letendre et al [8] (median improvement 0.29 while we found a median improvement of 0.47) in an open-label 12-week lithium study in patients with HAND.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium has further been shown to favorably influence other neurodegenerative diseases including Huntington´s chorea, Alzheimer´s disease, Parkinson´s disease, amyotrophic lateral sclerosis as well as spinocerebellar ataxias type 1 and type 3 [28-30, 64, 65]. Mechanisms invoked in the neuroprotective effect of lithium include direct or Akt-mediated inhibition of glycogen synthase kinase GSK-3β, Akt-mediated inhibition of the proapoptotic forkhead box class O transcription factor Foxo3a and murine double minute (MDM), stimulation of production and activity of neuroprotective brain derived neurotrophic factor BDNF, up-regulation of antiapoptotic protein Bcl-2, as well as down-regulation of proapoptotic transcription factor p53, of the proapoptotic proteins Bad and Bax, of glutamate excitotoxicity, of calpain and of oxidative stress [30,66]. The stimulating effect of NFκB on Orai1/STIM1 expression, I CRAC and SOCE observed here could, at least in theory, impact on neuronal cell survival and contribute to the beneficial effect of lithium.…”
Section: Discussionmentioning
confidence: 99%
“…Orai1 and SOCE are up-regulated by PI3K dependent signaling and thus sensitive to chorein [24]. Stimulators of Orai1 expression and SOCE include lithium [25][26][27], which may slow neurodegeneration [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Additional benefits of lithium therapy include neuroprotective [14,15], anti-inflammatory [16] and anti-apoptotic effects [17], which have been exploited to treat central nervous system trauma [18,19] and chronic neurodegenerative diseases, such as Huntington’s disease, amyotrophic lateral sclerosis and Parkinson’s disease [20,21]. In the peripheral nervous system, it has been shown that lithium administration can foster functional recovery and re-myelination after injury [22,23].…”
Section: Introductionmentioning
confidence: 99%